Molecular, serological, pathological, immunohistochemical and microbiological investigation of Brucella spp. in marine mammals of Brazil reveals new cetacean hosts - Sánchez-Sarmiento, Angélica M.; Carvalho, Vitor L.; Díaz-Delgado, Josué; Ressio, Rodrigo A.; Fernandes, Natália C. C. A.; Guerra, Juliana M.; Sacristán, Carlos; Groch, Kátia R.; Silvestre-Perez, Natalia; Ferreira-Machado, Eduardo; Costa-Silva, Samira; Navas-Suárez, Pedro; et al. (Hindawi, 2019)
Brucella-exposure and infection is increasingly recognized in marine mammals worldwide. To better understand the epidemiology and health impacts of Brucella spp. in marine mammals of Brazil, molecular (conventional PCR and/or real-time PCR), serological (Rose Bengal Test [RBT], Competitive [c]ELISA, Serum Agglutination Test [SAT]), pathological, immunohistochemical (IHC) and/or microbiological investigations were conducted in samples of 129 stranded or by-caught marine mammals (orders Cetartiodactyla [n = 124], Carnivora [n = 4] and Sirenia [n = 1]). Previous serological tests performed on available sera of 27 of the 129 animals (26 cetaceans and one manatee), indicated 10 seropositive cetaceans. Conventional PCR and/or real-time PCR performed in cases with available organs (n = 119) and/or blood or swabs (n = 10) revealed 4/129 (3.1%) Brucella-infected cetaceans (one of them with positive serology; the remaining three with no available sera). Pathological, IHC and/or microbiological analyses conducted in PCR/real-time PCR and/or seropositive cases (n = 13) revealed Brucella-type lesions, including meningitis/meningoencephalitis, pneumonia, necrotizing hepatitis, pericarditis and osteoarthritis in some of those animals, and positive IHC was found in all of them (excepting two live-stranded animals without available organs). Brucella spp. culture attempts were unsuccessful. Our results demonstrated exposure, asymptomatic, acute and chronic Brucella sp. infection in several cetacean species in the Brazilian coast, highlighting the role of this pathogen in stranding and/or death, particularly in Clymene dolphin (Stenella clymene) and short-finned pilot whale (Globicephala macrorhynchus) off Ceará State. Novel hosts susceptible to Brucella included the franciscana (Pontoporia blainvillei), the Guiana dolphin (Sotalia guianensis) and the spinner dolphin (Stenella longirostris). Additionally, three coinfection cases involving Brucella spp. and cetacean morbillivirus, Edwarsiella tarda and Proteus mirabilis were detected. To the best of our knowledge, this is the first long-term and large-scale survey of Brucella spp. in marine mammals of South America, widening the spectrum of susceptible hosts and geographical distribution range of this agent with zoonotic potential.
Keywords: Brucella spp.; cetacean morbillivirus; cetacean pathology; Edwarsiella tarda; immunohistochemistry; marine mammals; PCR; Proteus mirabilis